Enhancing referral processes within an integrated fall prevention pathway for older people: a mixed-methods study. Issue 8 (19th August 2022) - Flannery, Caragh; Dennehy, Rebecca; Riordan, Fiona; Cronin, Finola; Moriarty, Eileen; Turvey, Spencer; O'Connor, Kieran; Barry, Patrick; Jonsson, Agnes; Duggan, Eoin; O'Sullivan, Liz; O'Reilly, Éilis; et al.
Abstract : Objectives: Multifactorial interventions, which involve assessing an individual's risk of falling and providing treatment or onward referral, require coordination across settings. Using a mixed-methods design, we aimed to develop a process map to examine onward referral pathways following falls risk assessment in primary care. Setting: Primary care fall risk assessment clinics in the South of Ireland. Participants: Focus groups using participatory mapping techniques with primary care staff (public health nurses (PHNs), physiotherapists (PT), and occupational therapists (OT)) were conducted to plot the processes and onward referral pathways at each clinic (n=5). Methods: Focus groups were analysed in NVivo V.12 using inductive thematic analysis. Routine administrative data from January to March 2018 included details of client referrals, assessments and demographics sourced from referral and assessment forms. Data were analysed in Stata V.12 to estimate the number, origin and focus of onward referrals and whether older adults received follow-up interventions. Quantitative and qualitative data were analysed separately and integrated to produce a map of the service. Results: Nine staff participated in three focus groups and one interview (PHN n=2; OT n=4; PT n=3). 85 assessments were completed at five clinics (female n=69, 81.2%, average age 77). The average number of risk factors was 5.4 out of a maximum of 10. Following assessment, clients received an average of three onward referrals. Only one-third of referrals (n=135/201, 33%) had data available on intervention receipt. Primary care staff identified variations in how formally onward referrals were managed and barriers, including a lack of client information, inappropriate referral and a lack of data management support. Conclusion: Challenges to onward referral manifest early in an integrated care pathway, such as clients with multiple risk factors sent for initial assessment and the lack of an integrated IT system to share information across settings.